Analisis Strategi Pemasaran Edamame (Studi Kasus di UD.Lanusa, Denpasar) - FARIHA AMSA; RATNA KOMALA DEWI; IDA AYU LISTIA DEWI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2021)
Edamame Marketing Analysis (Case Study at UD. Lanusa, Denpasar) UD. Lanusa is one of the edamame suppliers in Bali that are supported by Dinas Pertanian Bali. UD. Lanusa located at Jalan Bypass Ngurah Rai No.174, Padang Galak, Sanur. The marketing areas of UD. Lanusa are Denpasar City and Badung Regency. UD. Lanusa aims to expand the marketing of edamame and reach the sales target of 100.00% with an average of 364.20 tons per year. However, UD. Lanusa could not achieve the target. SWOT analysis is the appropriate method to get the right marketing strategy. The result of this research shows that there are internal and external factors affecting edamame’s market of UD. Lanusa. There are eight strategies suggested from SWOT analysis. These alternatives give solutions based on internal and external factors that arise during the research process. It is recommended that UD. Lanusa maintains the quality of its edamame products, maximize variation and give a special design or logo on the packaging, review potential market areas, train employees to be able to use technologies such as the internet so they could promote edamame easily, and borrow the capital.